CrustChain: Resolving the blockchain trilemma via decentralized storage and proof-of-capacity consensus - Saha Reno; Koushik Roy (PLoS ONE, 2025)
The blockchain trilemma—achieving scalability, security, and decentralization simultaneously—remains an unsolved challenge in distributed systems. This paper introduces CrustChain, a novel framework that advances decentralized storage and consensus via three key innovations: (1) a reputation-weighted (where node influence scales with storage contribution and historical reliability) Proof-of-Capacity mechanism with temporal Sealed-Post (SPoSt) challenges, (2) hybrid erasure-network coding for 82% storage cost reduction, and (3) MDP-optimized sharding for sub-second cross-shard latency. By combining storage resource guarantees with a sharded validation layer, CrustChain processes 1,450 transactions per second (TPS) at sub-second latency while maintaining a chain quality score (fraction of blocks produced by honest nodes) of 0.94 under 40% Byzantine nodes. The system reduces on-chain storage overhead by 82% compared to Bitcoin through decentralized content addressing and Merkle forest compression. Experimental results demonstrate 99.99% data durability across 1,024 global nodes with $150 hardware requirements, achieving energy efficiency of 0.3 Joules per transaction (0.05% of Bitcoin’s consumption), and outperforming Filecoin’s storage costs by 63%. CrustChain’s layered architecture sets a new benchmark for blockchain systems requiring both high throughput and censorship resistance.